Albania : Insurance Market Development - World Bank Group (World Bank, Washington, DC, 2020)
The insurance industry in Albania is relatively new. Prior to 1991, there were no insurance companies operating in the country. The insurance industry has been undergoing critical changes during the last decade. The life market in Albania is small, and still dominated by credit life insurance. Life insurance was introduced only in 1997 and made up about seven percent of gross written premiums. Risk based supervision was rolled out in 2016, starting with comprehensive on-site inspections in three non-life insurance companies using the risk-focused methodology. The RBS method led to a market database that helps evaluate the risk profile of each insurance company, as well as the risk level of the insurance market as a whole. The country’s good economic development in the last two decades has contributed to the insurance market’s development, but so have good policy choices informed by technical assistance projects and other interventions by the World Bank Group and the FIRST trust fund. Without aspiring to the impossible task of attributing causal relationships between these interventions and specific market developments, this report will nonetheless suggest what role these interventions may have played in developing Albania’s insurance market, so as to guide the way forward in this country and future developmental strategies of other countries.